Dual Process Model of Coping With Bereavement in the Test of the Subjective Experiences of Bereaved Spouses: An Interpretative Phenomenological Analysis. (December 2016) - Fasse, Léonor; Zech, Emmanuelle
The Dual Process Model of Coping With Bereavement (DPM) was developed to better understand the dynamic coping processes adopted by bereaved people. In the present study, we investigated the daily subjective experiences of widowed people and examined whether they recognized themselves in the model. Thirteen out of the 16 interviewed widowed persons reported that their bereavement experience basically fitted the model. However, they also identified discrepancies. Interviews with six bereaved spouses were subjected to an interpretative phenomenological analysis. Three main issues were identified: (a) the interdependence versus distinctiveness of coping processes, (b) the conscious and intentional nature of coping strategies, and (c) the very nature of respite in the grief experience. The results indicated that, although relevant, the DPM did not always match the grieving experiences reported by the widowed individuals. Clinical and research perspectives are discussed.